P08 A Phase 1, randomized, double-blind study to evaluate the safety, tolerability, and immunogenicity of a 21-valent pneumococcal conjugate vaccine (PCV) (V116) in adults. (19th January 2023) - Platt, Heather; Fernsler, Doreen; Gallagher, Nancy; Sapre, Aditi; Polis, Adam; Hall, Lori; Tamms, Gretchen; Schwartz, Howard; Skinner, Julie; Joyce, Joseph; Murphy, Rocio; Musey, Luwy
Abstract: Background: V116, an investigational 21-valent PCV, contains the following pneumococcal polysaccharides (PnPs): 3, 6A, 7F, 8, 9N, 10A, 11A, 12F, 15A, 16F, 17F, 19A, 20, 22F, 23A, 23B, 24F, 31, 33F, 35B, and a de-O-acetylated 15B (deOAc15B). This phase 1 study evaluated the safety, tolerability, and immunogenicity of V116 in pneumococcal vaccine-naive adults compared with the 23-valent polysaccharide pneumococcal vaccine (PPSV23). Methods: Adults ( n =90) 18–49 years were randomized 1:1:1 to receive a single dose of V116-1 (2 μg dose/each PnPS, V116-2 (4 μg dose/PnPS) or PPSV23. Adverse events (AEs) were collected following vaccination. Pneumococcal serotype-specific opsonophagocytic activity (OPA) was measured prior to and 30 days postvaccination (Day 30). Results: There were no serious AEs, deaths, or discontinuations due to AEs. Immune responses at Day 30 in the V116-1 and V116-2 groups were generally comparable to PPSV23 for the common serotypes and higher than PPSV23 for the unique serotypes. At Day 30, the OPA GMTs were higher in the V116-2 group compared with the V116-1 group for all serotypes except 9N. The OPA geometric mean titre ratio (95% CI) (V116-2/PPSV23) ranged from 0.89 (0.58, 3.51) to 2.40 (1.24, 4.62) for all common serotypes and 2.80 (1.64, 4.79) to 58.07 (25.10, 134.33) for all unique serotypes; the lower bound of the 95% CI for the OPA GMT ratio (V116-2/PPSV23) was >0.5 for all common serotypes and >1.0 for all unique serotypes. Conclusions: These safety and immunogenicity data support the continued development of V116 for the prevention of pneumococcal disease in adults.